088 The clue is in the neck. Issue 6 (27th May 2022) - Cleaver, Jonathan; Morgan, Elsa; Lyons, Paul; Chohan, Gurjit
Abstract : Miller-Fisher Syndrome is characterised by ataxia, ophthalmoplegia and areflexia. Approximately 72% are preceded by infection, of which, Campylobacter jejuni and Haemophilus influenzae are frequently reported aetiological agents. We report a 22-year-old lady admitted with ataxia and worsening diplopia. On examination, she had bilateral abducens nerve palsies, left-sided facial weakness and widespread areflexia. Palpable lym- phadenopathy was present bilaterally. MRI showed mild inflammatory sinus disease and marked cervical lymphadenopathy. CSF revealed albuminocytologic dissociation and monospot was positive for Epstein-Barr virus. Subsequent abdominal sonography detected splenomegaly and counselling on avoiding contact sports was provided. A diagnosis of MFS was made based on the history, clinical features and supportive investigations. Anti-GQ1b antibodies were negative. MFS is typically associated with anti-GQ1b antibodies although a significant percentage (>10%) are seronegative. Recent studies have suggested anti-GAD may be associated with a broader clinical spectrum of presentations. The patient received 5 days of intravenous immunoglobulin and several weeks later she had complete symptomatic resolution. MFS is a self-limiting, though temporarily debilitating condition, and EBV should be remembered as a causative agent; particularly in susceptible demographic groups. Radiographic and viral clues, including examination of the neck, may facilitate accurate diagnosis. jkcleaver88@gmail.com